The effect of bio-stimulants and growth regulators on qualitative characteristics and germination of borage (Borago officinalis L.) seeds after storage - Mahrokh Bolandi; Parisa Sheikhzadeh; Saeed Khomari; Nasser Zare; Jaber Sharifi (علوم و فناوری بذر ایران, 2022)
To investigate the effect of the maternal plant's growth environment on qualitative characteristics and germination of borage seeds after storage, an experiment was carried out in a randomized complete block design with three replications at the University of Mohaghegh Ardabili. The treatments included seeds resulting from maternal plants sprayed with humic acid (0.5 g L-1), chitosan (1 g L-1), and the combination of humic acid and chitosan (0.5 g L-1 + 1 g L-1), salicylic acid. (4 mM), ascorbic acid (0.85 mM), potassium nitrate (20 mM) and control.The results showed that under non-storage conditions, the seeds that resulted from the maternal plants treated with bio-stimulants and growth regulators exhibited higher seed germination and seedling growth than those from the control plants. In this condition, foliar application of the maternal plants with humic acid+chitosan had the highest effect on the seed germination and seedling growth characteristics by increasing the germination percentage and rate, vigor index, seedlings dry weight and length. Although five years of dry seed storage reduced the seed viability and vigor, foliar application of maternal plants reduced the negative effects of storage on germination and enhanced the seed germination percentage and seedlings length, and dry weight by increasing the seed viability and seed vigor index. In general, among the foliar spraying treatments of the maternal plants, the combined foliar application of humic acid+chitosan, maybe due to the synergistic effects, can be considered the best treatment to improve the borage seed longevity, germination characteristics, and seedling growth.